Iranische Phytotherapie bei menopausalen Hitzewallungen - Uehleke, Bernhard (Zeitschrift für Phytotherapie, 2017)
ReferiertGhazanfarpour M, Sadeghi R, Abdolahian S, Latifnejad Roudsari R. The efficacy of Iranian herbal medicines in alleviating hot flashes: A systematic review. Int J Reprod Biomed (Yazd) 2016; 14: 155–166